Obstacles of applying digitization projects in the Algerian universities libraries: university libraries of the mandate of Constantine model - Saidi Ibtissam; Abd Elmalek Ben Sebti (Cybrarians Journal, 2016)
This study aims to identify the theoretical foundations of the concept of the digital and the requirements of their application in the Algerian university libraries. And disclosure of the most prominent organizational and technical, human and financial obstacles to the application of digitization in libraries Algerian universities in the state of Constantine This study has used a descriptive surveying approach and utilized the questionnaire as a technique for collecting information. Then work on the analysis and interpretation of the results obtained.